Sharp Estimation Type Inequalities for Lipschitzian Mappings in Euclidean Sense on a Disk. (8th February 2021) - Rostamian Delavar, M.; Dragomir, S. S.; De La Sen, M.
Abstract : Some sharp trapezoid and midpoint type inequalities for Lipschitzian bifunctions defined on a closed disk in Euclidean sense are obtained by the use of polar coordinates. Also, bifunctions whose partial derivative is Lipschitzian are considered. A new presentation of Hermite-Hadamard inequality for convex function defined on a closed disk and its reverse are given. Furthermore, two mappings H t and h t are considered to give some generalized Hermite-Hadamard type inequalities in the case that considered functions are Lipschitzian in Euclidean sense on a disk.